Perlindungan Hukum Bagi Debitur Wanprestasi Dalam Eksekusi Jaminan Fidusia Berdasarkan Undang-Undang Nomor 42 Tahun 1999 Tentang Fidusia - Daniel Romi Sihombing (Jurnal Media Justitia Nusantara, 2016)
The emergence of various financial institutions nowadays society helped spur the economy, but growth economic institutions are not supported by adequate legal development. Fiduciary Institute has recognized its existence with the Law of the Republic of Indonesia Number 42 Year 1999 regarding Fiduciary. Provision of financing for the debtor has the chance of risk. Fiduciary agreement is an agreement that arise because of the financing credit agreement (agreement inprincipal). If the debtor defaults, financial institutions can take on extinguishment of debt from the sale of collateral. The parties to the Fiduciary Security Agreement, both the receiver and giver of Fiduciary Fiduciary statutory fiduciary guarantees equally given legal protection, for the protection of the presence of the giver right to use the collateral objects, and in default the guarantor will not cause collateral objects with the Law Fiduciary. Focus includes problem identification, how the legal protection of debtors and creditors giver fiduciary fiduciary pursuant to Act No. 42 of 1999 concerning fiduciary? and how the efforts of law if the debtor defaults in agreement with the fiduciary and attempt to do if borrowers are in default? This study uses a method deskristifnormative and analytical nature. Based on the description and analysis of the problems it is known that the fiduciary protection for the giver, before declared in default by lenders is by doing a restructuring efforts, fostering dialogue between ourselves and the search for a solution, until the debtor is not defined in default. Safeguards for the debtor held as a joint venture by five principlesrelevant to national development, which as mentioned in the explanation of Article 2 of Law No. 8 of 1999 on Consumer Protection.Keywords: Legal Protection, Default, Execution, Fiduciary Guarantee